A Fully Verified Theoretical Analysis of Contact-Mode Triboelectric Nanogenerators as a Wearable Power Source - Yang, Bao; Zeng, Wei; Peng, Ze-Hua; Liu, Shi-Rui; Chen, Ke; Tao, Xiao-Ming (Advanced energy materials, 2016)
Harvesting mechanical energy from human activities by triboelectric nanogenerators (TENGs) is an effective approach for sustainable, maintenance‐free, and green power source for wireless, portable, and wearable electronics. A theoretical model for contact‐mode triboelectric nanogenerators based on the principles of charge conservation and zero loop‐voltage is illustrated. Explicit expressions for the output current, voltage, and power are presented for the TENGs with an external load of resistance. Experimental verification is conducted by using a laboratory‐fabricated contact‐mode TENG made from conducting fabric electrodes and polydimethylsiloxane/graphene oxide composite as the dielectric layer. Excellent agreements of the output voltage, current, and power are demonstrated between the theoretical and experimental results, without any adjustable parameters. The effects of the moving speed on output voltage, current, and power are illustrated in three cases, that is, the motion with constant speed, the sinusoidal motion cycles, and the real walking cycles by human subject. The fully verified theoretical model is a very powerful tool to guide the design of the device structure and selection of materials, and optimization of performance with respect to the application conditions of TENGs. A fully verified theoretical analysis of contact‐mode triboelectric generators with explicit expressions for the output current, voltage, and power is presented. Excellent agreements are demonstrated between the theoretical and experimental results without any adjustable parameters. The model is a powerful tool to guide the design of device structure, synthesis, and selection of materials, as well as optimization of performance.